PENGERTIAN, RUANG LINGKUP PERBANKAN, TUJUAN, LATAR BELAKANG, PRINSIP DAN SEJARAH PERBANKAN SYARIAH DI INDONESIA - Anggela Septiani; Heri Sunandar (Bajang Institute, 2023)
In the era of Law Number 10 of 1998, banking law policies in Indonesia adhered to a dual banking system. Research using qualitative methods in the library (library research). Sharia Banking aims to support the implementation of national development in order to improve justice, togetherness, and equal distribution of people's welfare. The legal basis for bank operations using the sharia system. The history of banking in Indonesia is actually the forerunner of conventional banking. This history began when Indonesia was colonized by the Dutch. At that time, there was already a bank called Bank Couranten Bank Van Leening. The bank's aim was to shoot and manage VOC finances. The Islamic bank that first appeared or stood in Indonesia was Bank Muamalat Indonesia. The principles of Islamic banking that are in accordance with Islamic law include the absence of elements of joy, maysir, gharar, and buying and selling of illicit goods. OJK's role in regulating and supervising banks is very broad in terms of microprudential regulation and supervision.